General practice trainee, supervisor and educator perspectives on the transitions in postgraduate training: a scoping review - Tran, Michael; Rhee, Joel; Hu, Wendy; Magin, Parker; Shulruf, Boaz (Family medicine and community health, 2024)
Transitions are a period and a process, through which there is a longitudinal adaptation in response to changing circumstances in clinical practice and responsibilities. While the experience of the transition in medical student learning and in hospital-based specialty training programmes are well described and researched, the experience of the transition in community-based postgraduate general practitioner (GP) training has not been described comprehensively.ObjectiveWe aimed to identify, and categorise, the formative experiences of transitions in GP training and their impacts on personal and professional development.DesignWe adopted Levac et al’s scoping review methodology. Of 1543 retrieved records, 76 were selected for data extraction. Based on a combined model of the socioecological and multiple and multi-dimensional theories of transitions, data relating to the experiences of transitions were organised into contextual themes: being physical, psychosocial, organisational culture and chronological.Eligibility criteriaEmpirical studies focused on general practice trainees or training, that discussed the transitions experienced in general practice training and that were published in English were included.Information sourcesPubMed, MEDLINE and Web of Science databases were searched in January 2024 with no date limits for empirical studies on the transition experiences of GP into, and through, training.ResultsOur findings describe context-dependent formative experiences which advance, or impede, learning and development. Time is a significant modulator of the factors contributing to more negative experiences, with some initially adverse experiences becoming more positive. Identification of the inflection point that represents a shift from initially adverse to more positive experiences of transitions may help moderate expectations for learning and performance at different stages of training.ConclusionChallenges in training can either advance development and contribute positively to professional identity formation and clinical competency, or detract from learning and potentially contribute to burnout and attrition from training programmes. These findings will assist future research in identifying predictive factors of positive and adverse experiences of transitions and may strengthen existing and nascent GP training programmes. The findings are transferable to other community-based specialty training programmes.